2012
DOI: 10.1016/j.bbamem.2011.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Gap junctional channels are parts of multiprotein complexes

Abstract: Gap junctional channels are a class of membrane channels composed of transmembrane channel-forming integral membrane proteins termed connexins, innexins or pannexins that mediate direct cell-to-cell or cell-to extracellular medium communication in almost all animal tissues. The activity of these channels is tightly regulated, particularly by intramolecular modifications as phosphorylations of proteins and via the formation of multiprotein complexes where pore-forming subunits bind to auxiliary channel subunits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
136
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(138 citation statements)
references
References 262 publications
1
136
0
Order By: Relevance
“…Indeed, it was reported in various cell types that the absence of Cx43 leads to a differential cellular transcriptome, which ultimately determines phenotyp- ical changes in cell morphology and cell adhesion suggesting that Cx43 has a direct role on gene transcription (6). On the other hand, studies carried out in osteosarcoma cell lines and in mouse bone marrow stromal cells (BMSCs), have shown that defects in GJIC may alter the subcellular localization and the recruitment of transcription factors to the promoter region of certain genes, impacting upon gene transcription (52,53).…”
Section: Table III Interaction Of Cx43 With Hnrnps Varies In Ischemiamentioning
confidence: 99%
“…Indeed, it was reported in various cell types that the absence of Cx43 leads to a differential cellular transcriptome, which ultimately determines phenotyp- ical changes in cell morphology and cell adhesion suggesting that Cx43 has a direct role on gene transcription (6). On the other hand, studies carried out in osteosarcoma cell lines and in mouse bone marrow stromal cells (BMSCs), have shown that defects in GJIC may alter the subcellular localization and the recruitment of transcription factors to the promoter region of certain genes, impacting upon gene transcription (52,53).…”
Section: Table III Interaction Of Cx43 With Hnrnps Varies In Ischemiamentioning
confidence: 99%
“…Connexins mediate intercellular communication through gap junction channels formed by two connexons that connect adjacent cells or as unopposed hemichannels, via the release of small molecules to the extracellular medium (2). The C terminus of connexin proteins faces the cytoplasm and through interactions with kinases and structural molecules participate in the regulation of intracellular signaling independently of channel activity (3).…”
mentioning
confidence: 99%
“…The cytoplasmic tails of many Cxs have also been shown to interact directly or indirectly with several proteins (10). Although these interactions have been postulated to control the assembly of Cxs into gap junctions, the molecular mechanisms involved have remained unexplored (10). In particular, it is not clear what the exact role of a Cx cytoplasmic tail is and at which step it is involved in regulating the assembly of gap junctions.…”
mentioning
confidence: 99%
“…The role of the two extracellular loop domains of Cxs in the formation of cell-to-cell channels as well as of the cytoplasmic tails in regulating the opening and closing of cell-cell channels has been well documented (5,(7)(8)(9). The cytoplasmic tails of many Cxs have also been shown to interact directly or indirectly with several proteins (10). Although these interactions have been postulated to control the assembly of Cxs into gap junctions, the molecular mechanisms involved have remained unexplored (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation